Uplatnění nepůvodních dřevin na narušených stanovištích: vliv stanovištních a krajinných faktorů - Prošková, Miloslava (Jihočeská univerzita, 2020)
The effect of local and landscape factors on establishment of alien woody species in various post-industrial sites in the Czech Republic was evaluated. The first part of the thesis was focused on the establishment and survival of late successional and alien woody seedling in differently restored sites (spontaneous succession vs forestry reclamation), each with various successional stages (young, middle, late), This part continued in the topic of Bc. Thesis to detect changes in a period up to three years since the establishment of the experiment. The second part, dealt with the invasive potential of selected alien woody species Quercus rubra, was studied in three abandoned post-mining sites represented by sand pits and compared with the species establishment in undisturbed afforested sites dominated by Pinus sylvestris. These two parts were conducted in Třeboňsko Protected Landscape Area. The last part evaluated the effect of local site and landscape factors at a broad national scale. For this purpose, the phytosociological relevés from Database of Successional Seres (DaSS) were used.
Establishment of alien woody species in disturbed sites: effect of local and landscape factors
Keywords: faktory prostředí; dřevina; nepůvodní druh; uchycení; Quercus rubra; landscape factors; woody species; alien species; establishment; Quercus rubra